Successful Preservation of Native BCR::ABL1 in Chronic Myeloid Leukemia Primary Leukocytes Reveals a Reduced Kinase Activity - Boni, Christian; Bonifacio, Massimiliano; Vezzalini, Marzia; Scaffidi, Luigi; Tomasello, Luisa; Parker, Laurie L.; Boscarino, Diego; Paladin, Dino; Krampera, Mauro; Sorio, Claudio (Frontiers in Oncology, 2022)
Chronic myeloid leukemia (CML) is a myeloproliferative disease caused by the acquisition of t(9;22) generating the fusion tyrosine kinase BCR::ABL1. However, despite the crucial role of this protein in the dysregulation of numerous signal transduction pathways, a direct measure of BCR::ABL1 kinase activity in chronic phase (CP) CML was never accomplished due to intense degradative activity present in mature leukocytes. Therefore, we developed a procedure suitable to preserve BCR::ABL1 protein under non-denaturing, neutral pH conditions in primary, chronic phase (CP)-CML samples. As a result, specific kinase activity was detected utilizing a biotinylated peptide substrate highly selective for c-ABL1. Furthermore, through this approach, BCR::ABL1 kinase activity was barely detectable in CP-CML compared to Ph+ acute lymphoblastic leukemia (ALL) primary samples, where kinase activity is comparable to those measured in Ph+ cell lines. These in vitro findings provide the first direct measure of BCR::ABL1 kinase activity in primary CP-CML and reveal the presence of a still uncharacterized inhibitory mechanism that maintains BCR::ABL1 in a low activity state in CP-CML despite its overexpression.